Konsep Penguatan Kepatuhan Masyarakat Terhadap Isolasi Mandiri Berbasis Pemberdayaan dan Partisipasi Masyarakat - Sutrisno Sutrisno; Sitti Nur Djannah; Solikhah Solikhah (Dian Nuswantoro Semarang, 2022)
Self-isolation is one of the efforts of the Indonesian Ministry of Health in handling the spread of Covid-19. This study aims to describe the behaviour of the community on compliance with the implementation of health protocols, especially related to self-isolation and to design a strategy for strengthening community compliance in self-isolation based on community empowerment and participation. The research was conducted using a qualitative method with a phenomenological approach. The research was conducted at Bumi Mulia Housing Estate, Semarangan, Sidokarto, Godean, Sleman, Yogyakarta. The participants involved in this study were all residents of the Bumi Mulia housing estate. Problems are identified through the measurement of community knowledge and behaviour, then followed up by making a conceptual framework and program of activities so that the community can jointly participate in participatory efforts to overcome the problems that have been identified in the previous stage. There are still problems related to community knowledge and behaviour in terms of self-isolation. Knowledge and attitudes that are not yet good in this case will affect the behaviour of the community regarding compliance with health protocols, especially related to self-isolation. Empowerment and community participation can be used as a strategy model in strengthening community groups to face health problems through community participation. With community empowerment and participation, people will be able to solve problems more effectively, independently, and organized to create conditions for people who are more prepared to face disasters. Keywords: Self-isolation, covid-19, community empowerment